Prototype home loan packages selection decision support system using financial model - Leong, Jenney (2005)
The process of choosing home loan packages is an important process for homebuyers. However, the process of choosing home loan packages is still being done manually. Actually, the traditional method used in the home loan packages choosing process is time consuming and troublesome to the homebuyers. However, the rapid growth of web technology has enabled proposed system to be applied as a competitive method to overcome the problem. Internet has become the channel for people to receive and convey information between each other in the decision making process. Prototype Home Loan Packages Selection Decision Support System Using Financial Model (HSDSS) is support system that using mathematical model (financial method) to allow user to explore the impact of available options. The optimal solution is obtained by using blind search with complete enumeration to check all the alternatives. This searching approach works together with weighted point system, so that the alternatives will have their weight of points after the searching is done. Based on the result of the ranking of the alternatives, HSDSS provides advices to the homebuyers on the matter of selecting suitable home loan packages. The use of this system will speed up and simplify how homebuyers make decision in choosing home loan packages, in addition to improving the competitive advantage for real estate service providers. As a conclusion, this system is capable in solving the current problems associated with choosing best suit home loan packages.